Lithium ion secondary battery

By using silicon carbon material and graphite negative electrode active layer in the electrode layer of lithium ion secondary battery, combining solid electrolyte with a specific particle size and positive electrode active layer of lithium cobalt oxide, the content ratio of Ti element and Al element is regulated, and the problems of poor discharge performance and insufficient high-temperature safety in low-temperature environments are solved, and a comprehensive improvement of high energy density, good low-temperature discharge performance and high-temperature safety is achieved.

CN120184350APending Publication Date: 2025-06-20ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510351256.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries have poor discharge performance in low-temperature environments and insufficient high-temperature safety.

Method used

Using a negative electrode active layer including silicon carbon material and graphite, combined with a solid electrolyte of a specific particle size and a positive electrode active layer of lithium cobalt oxide, the electrode structure of the battery is optimized to improve low-temperature discharge performance and high-temperature safety by regulating the content ratio of Ti elements and Al elements.

Benefits of technology

While ensuring a higher energy density, the low-temperature discharge performance and high-temperature safety of lithium-ion secondary batteries are significantly improved, solving the performance problems of the battery at extreme temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120184350A_ABST
    Figure CN120184350A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of secondary batteries, and discloses a lithium ion secondary battery. The lithium ion secondary battery comprises a positive plate and a negative plate, a negative active material in the negative plate comprises a silicon carbon material and graphite, and the content C of silicon element is 1-20% by taking the mass of a negative active layer as a reference; a positive active layer in the positive plate comprises lithium cobalt oxide and a solid-state electrolyte, the solid-state electrolyte comprises 2-40% of Ti element, and the maximum particle size D1 of the solid-state electrolyte is 500 nm to 3 [mu] m; the lithium cobalt oxide comprises a Ti element and an Al element, and the particle size Dv10 of the lithium cobalt oxide is greater than the average particle size D2 of the solid electrolyte; on the basis of the mass of the positive electrode active layer, the content of the Ti element is A ppm, the content of the Al element is B ppm, and A / B is larger than 0.05 and smaller than or equal to 0.3. The lithium ion secondary battery can solve the problems of poor low-temperature discharge performance and poor high-temperature safety of the existing lithium ion secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the technical field of secondary batteries, and particularly relates to a lithium-ion secondary battery. Background Art

[0002] With the rapid development of electric vehicles, portable electronic devices, and energy storage systems, the performance requirements for secondary batteries (such as lithium-ion secondary batteries) are increasing day by day, especially for the energy density and endurance time of the batteries. Energy density is one of the key factors determining the battery's endurance ability, and the core of improving energy density lies in optimizing the positive and negative electrode materials of the battery. Currently, the negative electrode active material of commercial lithium-ion secondary batteries mainly uses graphite, with a theoretical specific capacity of 372 mAh / g. Although it has good cycle stability and conductivity, its energy density has approached the theoretical limit and it is difficult to meet the requirements of future high-energy density batteries.

[0003] The theoretical specific capacity of silicon is as high as 4200 mAh / g, much higher than that of graphite, and it is considered an ideal candidate for the next-generation high-energy density negative electrode active material. However, due to the large volume change of silicon materials during charge and discharge, especially in high-temperature environments, it is easy to cause damage to the internal structure of the battery, making lithium-ion secondary batteries with graphite-doped silicon negative electrodes face problems such as battery swelling and leakage. Moreover, compared with graphite, the conductivity of silicon-carbon materials is poor, especially in low-temperature environments, and the electrochemical performance of silicon-carbon materials will further deteriorate, thus affecting the low-temperature discharge performance of the battery. Summary of the Invention

[0004] Therefore, the technical problem to be solved by this application is to overcome the defects of poor low-temperature discharge performance and high-temperature safety of existing lithium-ion secondary batteries.

[0005] For this reason, this application provides the following technical solutions.

[0006] This application provides a lithium-ion secondary battery, including a positive electrode sheet and a negative electrode sheet. The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer provided on at least one surface of the negative electrode current collector. The negative electrode active layer includes a negative electrode active material, and the negative electrode active material includes a silicon-carbon material and graphite. Based on the mass of the negative electrode active layer, the content of silicon element is C, and C is 1% to 20%;

[0007] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer provided on at least one surface of the positive electrode current collector. The positive electrode active layer includes a positive electrode active substance and a solid electrolyte, and the maximum particle size D1 of the solid electrolyte is 500 nm to 3 μm;

[0008] The solid electrolyte includes Ti element, and the mass content of the Ti element in the solid electrolyte is 2% to 40%;

[0009] The positive electrode active material includes lithium cobaltate, and the lithium cobaltate includes Ti element and Al element; the particle size Dv10 of the lithium cobaltate is greater than the average particle size D2 of the solid electrolyte;

[0010] Based on the mass of the positive electrode active layer, the content of the Ti element is A ppm, and the content of the Al element is B ppm, satisfying 0.05 < A / B ≤ 0.3.

[0011] In some embodiments, 0.1 ≤ A / B ≤ 0.2 is satisfied.

[0012] In some embodiments, the maximum particle size D1 of the solid electrolyte is 0.5 μm to 2 μm.

[0013] In some embodiments, the content C of silicon element in the negative electrode active layer is 1% to 20%.

[0014] In some embodiments, the ratio of A of the content A ppm of Ti element in the positive electrode active layer to the mass content C of silicon element in the negative electrode active layer satisfies 1250 ≤ A / C ≤ 130000.

[0015] In some embodiments, the solid electrolyte includes at least one of lithium aluminum titanium phosphate and lithium lanthanum titanium oxide.

[0016] In some embodiments, the mass content of the solid electrolyte in the positive electrode active layer is 0.1% to 2%.

[0017] In some embodiments, the lithium cobaltate includes first particles, and the particle size D3 of the first particles is 8 μm to 40 μm; a plurality of the solid electrolyte particles are distributed around the first particles, and the vertical distance between the solid electrolyte particles and the first particles is 0 to 6 μm.

[0018] In some embodiments, the content A ppm of Ti element in the positive electrode active layer satisfies 500 ≤ A ≤ 2000.

[0019] In some embodiments, the content B ppm of Al element in the positive electrode active layer satisfies 5000 ≤ B ≤ 10000.

[0020] In some embodiments, the particle size Dv10 of the lithium cobaltate is 2 μm to 5 μm.

[0021] In some embodiments, the median particle size Dv50 of the lithium cobaltate is 10 μm to 20 μm.

[0022] In some embodiments, the positive electrode active layer further includes a first conductive agent, the first conductive agent includes carbon nanotubes, and based on the mass of the positive electrode active layer, the content of the carbon nanotubes is 0.1% to 2%.

[0023] In some embodiments, the carbon nanotubes have a diameter of 5 nm to 100 nm.

[0024] In some embodiments, the mass content of silicon element in the silicon-carbon material is 35% to 70%.

[0025] In some embodiments, the graphite includes one or more of artificial graphite and natural graphite.

[0026] In some embodiments, the silicon-carbon material includes a carbon substrate and silicon particles dispersed in the pores of the carbon substrate.

[0027] In some embodiments, the negative electrode active layer further includes a second conductive agent, the second conductive agent includes single-walled carbon nanotubes, and the single-walled carbon nanotubes have a diameter of 1-50 nm.

[0028] In some embodiments, based on the mass of the negative electrode active layer, the content of the single-walled carbon nanotubes is 0.01% - 3%.

[0029] In some embodiments, the lithium ion secondary battery further includes an electrolyte, the electrolyte includes a solvent, the solvent includes ethyl propionate, and based on the mass of the electrolyte, the content of ethyl propionate is 20% to 60%.

[0030] In some embodiments, the positive electrode sheet further includes a positive electrode tab, the positive electrode tab is electrically connected to the positive electrode current collector, and the positive electrode tab extends from one side in the width direction of the positive electrode current collector. The width direction refers to the direction along the short side of the positive electrode current collector.

[0031] The lithium ion secondary battery further includes a separator, and the positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound into a core; at least one surface of the core in the thickness direction is provided with an adhesive, and the projections of the adhesive and the positive electrode tab in the thickness direction of the core are arranged in a dislocation manner along the height direction of the core.

[0032] In some embodiments, the shortest distance between the projections of the positive electrode tab and the adhesive in the thickness direction of the core is S, satisfying 100 mm ≥ S > 0.

[0033] In some embodiments, the bonding member has a first end close to the positive tab in the height direction of the core, and the positive current collector has a second end close to the positive tab in the height direction of the core. The distance between the first end and the second end in the height direction of the core is K, satisfying 125 mm ≥ K > 15 mm. The width direction of the positive current collector is consistent with the height direction of the core.

[0034] In some embodiments, the bonding member includes hot melt adhesive.

[0035] The technical solution of the present application has the following advantages:

[0036] The lithium-ion secondary battery of the present application includes a positive electrode sheet and a negative electrode sheet. The negative electrode sheet includes a negative current collector and a negative active layer provided on at least one surface of the negative current collector. The negative active layer includes a negative active material, and the negative active material includes a silicon-carbon material and graphite. Based on the mass of the negative active layer, the content of silicon element is C, and C is 1% to 20%; the positive electrode sheet includes a positive current collector and a positive active layer provided on at least one surface of the positive current collector. The positive active layer includes a positive active substance and a solid electrolyte. The maximum particle size D1 of the solid electrolyte is 500 nm to 3 μm; the solid electrolyte includes Ti element, and the mass content of the Ti element in the solid electrolyte is 2% to 40%; the positive active substance includes lithium cobaltate, and the lithium cobaltate includes Ti element and Al element; the particle size Dv10 of the lithium cobaltate is greater than the average particle size D2 of the solid electrolyte; based on the mass of the positive active layer, the content of the Ti element is A ppm, and the content of the Al element is B ppm, satisfying 0.05 < A / B ≤ 0.3.

[0037] The research of the present application finds that adding an appropriate amount of solid electrolyte with a specific particle size to the positive active layer can make up for the defect of poor low-temperature discharge performance of the battery caused by the decrease in the conductivity of the electrolyte. By reasonably controlling the maximum particle size D1 of the solid electrolyte particles within the range of 0.5 μm - 3 μm, the low-temperature discharge performance of the battery can be effectively improved. Combining with the graphite-doped silicon negative electrode can improve the energy density of the battery. The lithium-ion secondary battery provided by the present application can improve the low-temperature discharge performance while ensuring a relatively high energy density. Moreover, the average particle size D2 of the solid electrolyte is smaller than the particle size Dv10 of the lithium cobaltate, which can reduce the possibility of agglomeration between the solid electrolyte and the lithium cobaltate. The uniformly distributed solid electrolyte can still maintain good ionic conductivity at low temperature, thereby more effectively improving the conductivity of the positive active layer at low temperature and enhancing the low-temperature discharge performance of the battery. At the same time, by regulating the value of A / B to be greater than 0.05 and less than or equal to 0.3, the low-temperature discharge performance and high-temperature safety of the battery can be taken into account. The lithium-ion secondary battery provided by the present application can improve the low-temperature discharge performance and high-temperature safety while ensuring a relatively high energy density.

[0038] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the following description, or will be explained by the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the specific embodiments of the present application or the technical solutions in the prior art, the following will briefly introduce the drawings required for use in the description of the specific embodiments or the prior art. Obviously, the drawings in the following description are some embodiments of the present application. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0040] Figure 1 SEM diagram of the positive electrode sheet in Example 5;

[0041] Figure 2 Magnified SEM diagram of the positive electrode sheet in Example 5;

[0042] Figure 3 Schematic top view of the core;

[0043] Figure 4 Front view of the core.

[0044] Reference Signs:

[0045] 1 - Bonding member; 2 - Positive electrode tab; 3 - Solid electrolyte particles; 4 - Lithium cobaltate particles; S - Shortest distance between the projection of the positive electrode tab and the bonding member in the thickness direction of the core; K - Distance between the first end and the second end along the height direction of the core. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0046] The following embodiments are provided to better further understand the present application. They are not limited to the best embodiments, and do not limit the content and protection scope of the present application. Any product that is the same as or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with those of other prior arts falls within the protection scope of the present application.

[0047] For those embodiments where specific experimental steps or conditions are not indicated, the operations or conditions of the conventional experimental steps described in the literature in this field can be followed. For reagents or instruments whose manufacturers are not indicated, they are all conventional reagent products that can be obtained through commercial purchase.

[0048] The related technology adds solid electrolytes to the electrode plates of lithium-ion secondary batteries, thereby constructing a solid electrolyte layer on the surface of the electrode material layer, strengthening the conductivity of lithium ions at the positive / negative electrode interface, optimizing the conductivity of the electrolyte system, and thus improving the rate performance of the battery. By mixing solid electrolytes into the electrode plates, the use of liquid electrolytes is reduced, and the high-temperature safety performance of the battery is enhanced. However, the above technology does not examine the low-temperature discharge performance of the battery. As the temperature decreases, the ionic conductivity of the electrolyte decreases significantly, especially below 0°C, the ionic conductivity of the electrolyte will drop drastically. In addition, the poor conductivity of the silicon-carbon material itself is not conducive to the diffusion of lithium ions, further deteriorating the low-temperature discharge performance of the battery. That is, lithium-ion secondary batteries using graphite-doped silicon-carbon negative electrodes face the problem of being unable to discharge normally in extreme low-temperature weather (for example, temperatures below -20°C).

[0049] To solve the above problems, the present application provides a lithium ion secondary battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active layer comprises a negative electrode active material, wherein the negative electrode active material comprises a silicon-carbon material and graphite, and based on the mass of the negative electrode active layer, the content of silicon element is C, and C is 1% to 20%; illustratively, the content C of silicon element in the negative electrode active layer can be 1%, 5%, 10%, 15%, 20%, etc., or a value within the range formed by any two of the above values;

[0050] The positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active layer comprises a positive electrode active material and a solid electrolyte, and the maximum particle size D1 of the solid electrolyte is 500 nm to 3 μm;

[0051] The solid electrolyte includes a Ti element, and the mass content of the Ti element in the solid electrolyte is 2% to 40%;

[0052] The positive electrode active material includes lithium cobalt oxide, and the lithium cobalt oxide includes Ti and Al elements; the particle size Dv10 of the lithium cobalt oxide is greater than the average particle size D2 of the solid electrolyte;

[0053] Based on the mass of the positive electrode active layer, the content of the Ti element is Appm, and the content of the Al element is B ppm, satisfying 0.05<A / B≤0.3.

[0054] It is found in the research of this application that the ionic conductivity of the solid electrolyte does not decrease significantly with the decrease of temperature. By adding an appropriate amount of solid electrolyte with a specific particle size to the positive electrode active layer, lithium ions can be conducted along the solid electrolyte under extremely low temperature conditions, thereby replacing part of the conduction path of the electrolyte, ensuring that the battery can discharge normally under low temperature conditions, and making up for the defect of poor low-temperature discharge performance of the battery caused by the decrease of electrolyte conductivity.

[0055] The maximum particle size D1 of the solid electrolyte has an important influence on the improvement effect of the low-temperature discharge performance of the battery. If the particle size of the solid electrolyte particles is too large, the ability to conduct lithium ions will decrease. On the contrary, if the particle size is too small, the particles are prone to agglomeration, and neither can play a role in improving the low-temperature discharge performance of the battery. Therefore, by reasonably controlling the maximum particle size D1 of the solid electrolyte particles within the range of 0.5 μm - 3 μm, the low-temperature discharge performance of the battery can be effectively improved. Combining with the silicon-doped graphite negative electrode can improve the energy density of the battery. Therefore, the lithium-ion secondary battery provided by this application can improve the low-temperature discharge performance while ensuring a relatively high energy density. Exemplarily, the maximum particle size D1 of the solid electrolyte can be 500 nm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, etc. or a value within the range composed of any two of the above values.

[0056] Moreover, the average particle size D2 of the solid electrolyte is smaller than the particle size Dv10 of lithium cobaltate, that is, the solid electrolyte particles are smaller and the lithium cobaltate particles are larger. This particle size grading reduces the contact area between the particles, reduces the possibility of agglomeration between the solid electrolyte and lithium cobaltate, and the small-particle solid electrolyte is more likely to be evenly dispersed around the large-particle lithium cobaltate, so as to better fill the gaps between the lithium cobaltate particles, form a continuous ion conduction path, and improve the ion transport efficiency; because the evenly distributed solid electrolyte can still maintain good ionic conductivity at low temperature, it can more effectively improve the conductivity of the positive electrode active layer at low temperature and improve the low-temperature discharge performance of the battery.

[0057] Meanwhile, the research of this application finds that the value of the ratio A / B of the content of Ti element to the content of Al element in the positive electrode active layer will affect the low-temperature discharge performance and high-temperature safety of the battery. The Ti element can improve the conduction of lithium ions. Especially at low temperatures, introducing the Ti element can reduce the migration energy barrier of lithium ions and enhance the ionic conductivity of the positive electrode active layer, so that the battery still has a high discharge capacity under low-temperature conditions. However, an excessive amount of Ti element will affect the discharge capacity of the battery in a normal-temperature environment, thereby affecting the energy density. Moreover, when the solid electrolyte is stored in a high-temperature and high-voltage environment, gas is easily generated, affecting the safety performance of the battery. The Al element can stabilize the layered structure of lithium cobaltate and inhibit the phase change and oxygen release of lithium cobaltate at high temperatures, thereby improving the high-temperature safety of the battery. An appropriate amount of Al element has little effect on the low-temperature performance, but an excessive amount of Al element may increase the migration resistance of lithium ions and reduce the ionic conductivity at low temperatures. Therefore, by controlling the value of A / B to be greater than 0.05 and less than or equal to 0.3, the low-temperature discharge performance and high-temperature safety of the battery can be taken into account.

[0058] If the value of A / B is too small, that is, the content of Ti element is too low or the content of Al element is too high, the low-temperature discharge performance cannot be effectively improved. If the value of A / B is too large, that is, the content of Ti element is too high or the content of Al element is too low, the high-temperature safety of the battery may be poor. Exemplarily, the value of A / B can be 0.06, 0.10, 0.15, 0.20, 0.25, 0.30, etc. or a value within the range composed of any two of the above values.

[0059] By controlling the mass content of Ti element in the solid electrolyte to be 2%-40%, the addition amount of the solid electrolyte can be reduced on the basis of ensuring the content of Ti element in the positive electrode active layer, thereby increasing the content of lithium cobaltate in the positive electrode active layer, and thus improving the specific capacity and energy density of the battery while improving the low-temperature discharge performance of the battery. If the mass content of Ti element in the solid electrolyte is too low, it is not sufficient to significantly improve the ionic conductivity of the electrolyte, it is difficult to improve the low-temperature discharge performance of the battery, and the content of the solid electrolyte to be added is too high, resulting in a decrease in the proportion of the positive electrode active material and ultimately a decrease in the energy density of the battery. If the mass content of Ti element in the solid electrolyte is too high, it may also form too many insulating phases, resulting in a decrease in the ionic conductivity of the electrolyte, and instead, an increase in the electrolyte dosage is required to make up for the performance loss, thereby reducing the energy density. Exemplarily, the content of Ti element in the solid electrolyte can be 2wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, etc. or a value within the range composed of any two of the above values.

[0060] In summary, the lithium-ion secondary battery provided by this application can improve the low-temperature discharge performance and high-temperature safety while ensuring a high energy density.

[0061] It should be noted that the maximum particle size D1 refers to the maximum diameter of the solid electrolyte particles within the observation field of a scanning electron microscope (SEM). The test method for D1 includes: after discharging the lithium-ion secondary battery to 0% SOC, disassembling and taking out the positive electrode sheet, soaking it in dimethyl carbonate (DMC) solvent for 12 h and then rinsing it with DMC to remove the lithium salts attached to the electrode sheet (the lithium salts present in the electrolyte and attached to the positive electrode sheet), and using an argon ion milling instrument CP to laser cut the positive electrode sheet; using an energy dispersive spectrometer (EDS) for area scanning to find the position where Ti element is enriched, and performing point scanning at a magnification of 5K. The particles with the total content of Ti element in the enriched position within the range of 2 wt% to 40 wt% are solid electrolyte particles, and then observing at a magnification of 5K in the SEM. The maximum diameter of the solid electrolyte particles within the field of view is recorded as D1.

[0062] The average particle size D2 refers to the average value of the particle sizes of 10 solid electrolyte particles within the observation field of the SEM. The test method for D2 includes: after discharging the lithium-ion secondary battery to 0% SOC, disassembling and taking out the positive electrode sheet, soaking it in dimethyl carbonate (DMC) solvent for 12 h and then rinsing it with DMC to remove the lithium salts attached to the electrode sheet, and using an argon ion milling instrument CP to laser cut the positive electrode sheet; using EDS for area scanning to find the position where Ti element is enriched, and performing point scanning at a magnification of 5K. The particles with the total content of Ti element in the enriched position within the range of 2 wt% to 40 wt% are solid electrolyte particles; then observing at a magnification of 5K in the SEM. If there are more than 10 solid electrolyte particles within the field of view, randomly select 10 solid electrolyte particles to calculate their average particle size, which is recorded as D2; if the number of solid electrolyte particles within the field of view is less than 10, change the field of view position and retest.

[0063] Among them, the content of Ti element in the solid electrolyte is measured by EDS. The test method includes: after discharging the lithium-ion secondary battery to 0% SOC, disassembling and taking out the positive electrode sheet, soaking it in dimethyl carbonate (DMC) solvent for 12 h and then rinsing it with DMC to remove the lithium salts attached to the electrode sheet (the lithium salts present in the electrolyte and attached to the positive electrode sheet), and using an argon ion milling instrument CP to laser cut the positive electrode sheet; performing point scanning on the solid electrolyte particles at a magnification of 5K using an energy dispersive spectrometer (EDS), and thus measuring the Ti content in the solid electrolyte.

[0064] The test method for the content of Ti element and Al element in the positive electrode active layer is as follows: After discharging the lithium-ion secondary battery to 0% SOC, disassemble and take out the positive electrode plate, soak it in dimethyl carbonate (DMC) solvent for 12 h, and then rinse it with DMC to remove the lithium salts attached to the electrode plate. After calcining at 400 °C in a high-temperature muffle furnace for 3 h, gently scrape off the residual substances of the positive electrode active layer from the surface of the positive electrode current collector. According to the method in GBT 30902-2014, configure the residual substances of the positive electrode active layer into a standard solution, and then measure the concentrations of Ti element and Al element in the standard solution according to the test method of GBT 30902-2014, which are the contents of Ti element and Al element in the positive electrode active layer. The content of Ti element is recorded as A ppm, and the content of Al element is recorded as B ppm.

[0065] The particle size Dv10 is the particle size corresponding to the cumulative volume distribution of lithium cobaltate particles reaching 10%, and the particle size Dv50 is the particle size corresponding to the cumulative volume distribution of lithium cobaltate particles reaching 50%. The test method includes: After discharging the lithium-ion secondary battery to 0% SOC, disassemble and take out the positive electrode plate, soak it in dimethyl carbonate (DMC) solvent for 12 h, and then rinse it with DMC to remove the lithium salts attached to the electrode plate. After calcining at 400 °C in a muffle furnace for 3 h, gently scrape off the residual substances of the positive electrode active layer from the surface of the positive electrode current collector to obtain a composite material, and use a Malvern particle size tester for measurement. The test steps are as follows: Disperse the composite material in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether, with a content of 0.02-0.03 wt%) to form a mixture, ultrasonically treat the mixture for 2 minutes, and then put it into the Malvern particle size tester for testing.

[0066] The test method for the mass content C of silicon element in the negative electrode active layer: It is tested by thermogravimetric analysis. The specific method is as follows: After discharging the lithium-ion secondary battery to 0% SOC, disassemble and take out the negative electrode plate, soak it in dimethyl carbonate (DMC) solvent for 12 h, and then rinse it with DMC to remove the lithium salts attached to the electrode plate. After drying, heat-treat the electrode plate at 400 °C in an inert atmosphere for 2 h (such as in a tube furnace under nitrogen or argon atmosphere), and the negative electrode active material layer can be peeled off from the current collector, and the negative electrode active material is collected. In the silicon content test, use a thermogravimetric analyzer (such as TGA 550 thermogravimetric analyzer), the sample amount for testing is 5-15 mg, in air or oxygen atmosphere, heat from room temperature to 900 °C at a heating rate of 10 °C / min, and keep it at 900 °C for 40 min, so that the non-silicon components in the negative electrode material active layer volatilize while silicon can be fully oxidized to silicon dioxide. The weight percentage at the end of the whole test process is the ash content of the negative electrode active layer; divide the ash value by the molar mass of silicon dioxide (60) and then multiply by the molar mass of silicon (28) to obtain the percentage content of silicon in the negative electrode active layer.

[0067] In some embodiments, the content of Ti element in the positive electrode active layer, A ppm, satisfies 500 ≤ A ≤ 2000. By controlling the content of Ti element in the positive electrode active layer within this range, while improving the lithium ion conductivity and enhancing the low-temperature discharge performance, the gas generation amount of the solid electrolyte under high-temperature and high-pressure environments can be reduced, and the high-temperature safety of the battery can be improved. If the content of Ti element is too low, the low-temperature discharge performance cannot be effectively improved; if the content of Ti element is too high, the high-temperature safety of the battery may be poor. By simultaneously controlling the content of Ti element and Al element in the positive electrode active layer, the low-temperature discharge performance and high-temperature safety of the battery can be taken into account. Exemplarily, the value of A can be 500, 800, 1000, 1500, 2000, etc. or a value within the range composed of any two of the above values.

[0068] In some embodiments, the content of Al element in the positive electrode active layer, B ppm, satisfies 5000 ≤ B ≤ 10000. By controlling the content of Al element in the positive electrode active layer within this range, the layered structure of lithium cobaltate can be stabilized, the phase change and oxygen release of lithium cobaltate at high temperatures can be inhibited, thereby improving the high-temperature safety of the battery while ensuring the low-temperature performance of the battery. If the content of Al element is too low, it is difficult to play a role in improving the high-temperature safety of the battery; if the content of Al element is too high, it may increase the migration resistance of lithium ions and reduce the ionic conductivity content at low temperatures, resulting in a decrease in the low-temperature discharge performance of the battery. By simultaneously controlling the content of Ti element and Al element in the positive electrode active layer, the low-temperature discharge performance and high-temperature safety of the battery can be taken into account. Exemplarily, the value of B can be 5000, 6000, 7000, 8000, 9000, 10000, etc. or a value within the range composed of any two of the above values.

[0069] In some embodiments, the content of silicon element C in the negative electrode active layer and the content of Ti element A ppm in the positive electrode active layer satisfy 1250 ≤ A / C ≤ 130000; Exemplarily, the value of A / C can be 1250, 2000, 10000, 20000, 50000, 80000, 100000, 110000, 130000, etc. or a value within the range composed of any two of the above values.

[0070] It can be understood that the higher the content of silicon element in the negative electrode active layer, the higher the energy density of the battery can be guaranteed, but the lower the low-temperature discharge performance of the battery. Correspondingly, more solid electrolyte needs to be added to the positive electrode active layer. By regulating the value of A / C within the above range in this application, the battery can have both a relatively high energy density, good low-temperature discharge performance and high-temperature safety. If the value of A / C is too large, it indicates that the content of silicon element in the negative electrode active layer is relatively small, which affects the energy density of the battery, or it indicates that the addition amount of the solid electrolyte in the positive electrode active layer is relatively large, and gas is easily generated during high-temperature storage, which affects the high-temperature safety of the battery; if the value of A / C is too small, it indicates that the content of silicon element in the negative electrode active layer is relatively large, which affects the low-temperature discharge performance of the battery, or it indicates that the addition amount of the solid electrolyte in the positive electrode active layer is relatively small, and the improvement effect on the low-temperature discharge performance of the battery is limited and cannot reach the optimal state.

[0071] In some embodiments, the Dv10 of the lithium cobaltate is 2 μm to 5 μm. Exemplarily, the Dv10 can be 2 μm, 1.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc. or a value within the range composed of any two of the above values.

[0072] When the Dv10 of the lithium cobaltate is too large, it indicates that the overall particle size of the lithium cobaltate particles is relatively large, and the lithium ion transmission path is too long, resulting in a decrease in the conductivity of the lithium cobaltate; while when the Dv10 is too small, it indicates that the overall particle size of the lithium cobaltate particles is relatively small, and particle agglomeration is likely to occur, which will also affect its conductivity, and the specific surface area of the small particles is relatively large, and the high-temperature safety is poor. Therefore, in this application, by regulating the Dv10 of the lithium cobaltate within the range of 2 μm to 5 μm, at this time, the proportion of large-particle lithium cobaltate is relatively large, which helps to improve the high-temperature safety, but will affect the conductivity. By adding a solid electrolyte, the adverse effect of large-particle lithium cobaltate on the conductivity can be compensated, so that the battery can further balance the low-temperature discharge performance and the high-temperature safety.

[0073] In some embodiments, the median particle size Dv50 of the lithium cobaltate is 10 to 20 μm, which can avoid the excessive thickness of the electrode sheet, is beneficial to improving the energy density of the battery, and helps the uniform diffusion of lithium ions at this particle size, reduces the internal resistance at high temperature, reduces heat accumulation, and improves the high-temperature performance. At the same time, it is also beneficial to ion conduction at low temperature and improves the low-temperature performance. In this application, by regulating the Dv10 and Dv50 of the lithium cobaltate particles and controlling the Dv10 of the lithium cobaltate to be greater than the average particle size D2 of the solid electrolyte, the solid electrolyte can be evenly dispersed around the large-particle lithium cobaltate, improving the ion transmission efficiency and the low-temperature discharge performance, while reducing the internal resistance at high temperature and improving the high-temperature performance of the battery. Exemplarily, the Dv50 can be 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, etc. or a value within the range composed of any two of the above values.

[0074] In some embodiments, the solid electrolyte includes at least one of lithium aluminum titanium phosphate and lithium lanthanum titanium oxide. Among them, the lithium aluminum titanium phosphate is a superionic conductor type lithium aluminum titanium phosphate, and its chemical formula can be Li 1+u Al u Ti 2-u (PO4)3, where 0 < u ≤ 0.5; the lithium lanthanum titanium oxide is a perovskite type lithium lanthanum titanium oxide, and its chemical formula can be Li 3v La 2 / 3-v TiO3, where 0 < v ≤ 0.2.

[0075] The above solid electrolyte has strong ion conduction ability and high dielectric constant, and has good affinity for the electrolyte. When it is applied to the positive electrode sheet, it can improve the ion transport ability of the positive electrode sheet at low temperature, so that the lithium ion secondary battery using a silicon-doped graphite negative electrode has both high energy density and good low-temperature discharge performance and high-temperature safety.

[0076] In some embodiments, the mass content of the solid electrolyte in the positive electrode active layer is 0.1% - 2.0%. Exemplarily, it can be 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, etc. or values within the range composed of any two of the above values.

[0077] If the content of the solid electrolyte in the positive electrode active layer is too low, the effect of improving the low-temperature discharge performance of the battery is not obvious; however, if the content of the solid electrolyte is too high, it will affect the discharge capacity of the battery in the normal temperature environment, and then affect the energy density. Moreover, the solid electrolyte is prone to gas generation during storage in a high-temperature and high-voltage environment, affecting the safety performance of the battery. Therefore, controlling the content of the solid electrolyte in the positive electrode active layer within the range of 0.1% - 2.0% can effectively improve the low-temperature discharge performance of the battery without losing energy density and high-temperature safety.

[0078] In some embodiments, the lithium cobaltate includes first particles and second particles. The particle size D3 of the first particles is 8 μm - 40 μm, and the particle size of the second particles is less than 8 μm; several solid electrolyte particles are distributed around the first particles, and the vertical distance between the solid electrolyte particles and the first particles is 0 - 6 μm.

[0079] It should be noted that the particle size D3 refers to the maximum distance between any two points on the contour of the lithium cobaltate particles. The test method for D3 includes: taking a particle image using SEM, analyzing the particle contour through image processing software (such as ImageJ), and measuring the maximum distance between any two points on the particle contour, which is the particle size D3. Exemplarily, D3 can be 8μm, 9μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, etc. or values within the range composed of any two of the above values.

[0080] Compared with the second particles (small lithium cobaltate particles), the first particles (large lithium cobaltate particles) have a longer internal transport path within the particles, resulting in lower ionic conductivity, which in turn affects the lithium ion transport. In response to this, during the preparation of the positive electrode paste in this application, by first mixing the solid electrolyte with lithium cobaltate and then adding other substances such as a conductive agent and a binder, it is ensured that the solid electrolyte is evenly distributed around the large lithium cobaltate particles, such that a plurality of the solid electrolyte particles are distributed around the large lithium cobaltate particles, and the vertical distance between the solid electrolyte particles and the large lithium cobaltate particles is 0 to 6μm, thereby improving the lithium ion transport network, further improving the ionic conductivity of the positive electrode active layer, and enhancing the low-temperature discharge performance of the battery.

[0081] In some embodiments, the positive electrode active layer further includes a first conductive agent, the first conductive agent includes carbon nanotubes, and the diameter of the carbon nanotubes is 5nm to 100nm. Due to the unique structure of carbon nanotubes, they have better conductive performance and lithium intercalation performance. By adding carbon nanotubes with a diameter of 5nm to 100nm to the positive electrode active layer, the low-temperature discharge performance and high-temperature safety of the battery can be further enhanced. The research in this application finds that if the diameter of the carbon nanotubes is too small, the carbon nanotubes are prone to agglomeration, making it difficult to form a conductive network, which is not conducive to the transport of lithium ions and also not conducive to reducing the internal resistance, affecting the low-temperature discharge performance and high-temperature safety of the battery; while if the diameter of the carbon nanotubes is too large, it will affect the crystallinity of the carbon nanotubes, resulting in unsatisfactory conductive performance, strength, and toughness, and thus being not conducive to the low-temperature discharge performance and high-temperature safety of the battery.

[0082] Moreover, when the solid electrolyte comes into contact with the electrolyte solution, a chemical reaction may occur, resulting in the formation of an interfacial layer, increasing the interfacial impedance, and affecting ion conduction. By using carbon nanotubes with a tube diameter of 5 nm to 100 nm, the distribution of the electrolyte solution in the positive electrode active layer can be restricted, the contact area between the electrolyte solution and the solid electrolyte can be reduced, thereby reducing the probability of side reactions. At the same time, the electron and ion conduction paths can be optimized by regulating the tube diameter of the carbon nanotubes, the addition amount of the solid electrolyte, etc., so as to improve the overall performance of the battery while suppressing side reactions. Exemplarily, the tube diameter of the carbon nanotubes can be 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc. or values within the range composed of any two of the above values.

[0083] In some embodiments, based on the mass of the positive electrode active layer, the content of the carbon nanotubes is 0.1% to 2%. Exemplarily, the content of the carbon nanotubes can be 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, etc. or values within the range composed of any two of the above values.

[0084] In some embodiments, the graphite includes one or more of artificial graphite and natural graphite.

[0085] The higher the silicon content in the silicon-doped graphite negative electrode, the more beneficial it is to improve the energy density of the battery, but it is not conducive to the diffusion of lithium ions in the negative electrode under low-temperature environments. Therefore, in some embodiments, the mass content of silicon elements in the silicon-carbon material is 35% - 70%. Exemplarily, it can be 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc. or values within the range composed of any two of the above values.

[0086] In order to balance the contradiction between the energy density and low-temperature discharge performance of the high-silicon negative electrode battery, by adding a solid electrolyte to the positive electrode active layer, lithium ions can be conducted along the solid electrolyte, replacing part of the conduction path of the electrolyte solution, ensuring that the battery can discharge normally under low-temperature conditions, thereby improving the low-temperature discharge performance of the battery while ensuring a high energy density of the battery.

[0087] In some embodiments, the silicon-carbon includes a carbon substrate and silicon particles dispersed in the pores of the carbon substrate. The carbon substrate includes porous carbon and a carbon layer coating at least part of the surface of the porous carbon. The silicon particles include one or more of Si, SiO2, SiO n wherein 0 < n < 2.

[0088] In some embodiments, the negative electrode active layer further includes a second conductive agent, the second conductive agent includes single-walled carbon nanotubes, and the diameter of the single-walled carbon nanotubes is 1 to 50 nm. Due to the unique structure of single-walled carbon nanotubes, they have better electrical conductivity and lithium intercalation performance. By adding single-walled carbon nanotubes with a diameter of 1 to 50 nm to the negative electrode active layer, a stable three-dimensional conductive network can be formed between silicon-carbon and graphite particles. This network can not only adapt to the volume change of silicon but also maintain the continuity of the electron conduction path during charge and discharge, thereby forming an efficient electron conduction path between the negative electrode active materials. That is, the mixture of single-walled carbon nanotubes and silicon-carbon particles can significantly improve the electron conduction ability of silicon-carbon and reduce the internal resistance. If the diameter of the single-walled carbon nanotubes is too small, the single-walled carbon nanotubes are prone to agglomeration, making it difficult to form a conductive network, which is not conducive to the transmission of electrons to the current collector and also not conducive to reducing the internal resistance, affecting the low-temperature discharge performance of the battery. While if the diameter of the single-walled carbon nanotubes is too large, it will affect the crystallinity of the single-walled carbon nanotubes, resulting in unsatisfactory electrical conductivity, strength, and toughness, and thus being unfavorable for the low-temperature discharge performance and high-temperature safety of the battery. Exemplarily, the diameter of the single-walled carbon nanotubes can be 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, etc. or values within the range composed of any two of the above values.

[0089] In some embodiments, the mass content of the single-walled carbon nanotubes in the negative electrode active layer is 0.01% to 3%. Exemplarily, the mass content of the single-walled carbon nanotubes in the negative electrode active layer can be 0.01%, 0.1%, 0.2%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, etc. or values within the range composed of any two of the above values.

[0090] In some embodiments, the electrolyte includes ethyl propionate (EP), and based on the mass of the electrolyte, the content of ethyl propionate is 20% to 60%. Exemplarily, the content of EP can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc. or values within the range composed of any two of the above values.

[0091] EP is a carboxylic acid ester solvent. Its characteristics of low boiling point and small viscosity enable EP to have good fluidity, which can reduce the viscosity of the electrolyte and facilitate the infiltration of the electrolyte into the electrode sheet. When the content of EP is too high, a large amount of gas is generated by high-temperature decomposition, which is likely to cause safety problems such as battery swelling. When the content is too low, the viscosity of the electrolyte is high, which is not conducive to infiltration and local lithium plating is likely to occur. When the content of EP is 20% - 60%, EP and the solid electrolyte act synergistically, which can further improve the low-temperature performance of the battery on the basis of doping the solid electrolyte to improve the low-temperature discharge performance. Moreover, when the negative electrode of the secondary battery is doped with silicon carbide, the prepared secondary battery has both high energy density and higher low-temperature discharge performance.

[0092] In some embodiments, it further includes a separator and a positive electrode tab. The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound to form a wound core. The positive electrode tab is electrically connected to the positive electrode sheet, and the positive electrode tab extends from one side in the width direction of the positive electrode sheet.

[0093] At least one side surface in the thickness direction of the wound core is provided with an adhesive. The projections of the adhesive and the positive electrode tab in the thickness direction of the wound core are arranged in a dislocation manner along the height direction of the wound core. The adhesive is used for bonding the wound core to the housing.

[0094] In some embodiments, 100mm ≥ S > 0, where S is the shortest distance between the projections of the positive electrode tab and the adhesive in the thickness direction of the wound core. Exemplarily, S can be 2mm, 5mm, 8mm, 10mm, 50mm, 80mm, 100mm, etc. or a value within the range composed of any two of the above values. The height direction of the wound core is as Figure 3 shown, and the thickness direction of the wound core is as Figure 4 shown.

[0095] The thickest position of the wound core often appears at the electrode tab. If the adhesive coincides with the electrode tab, it will cause an increase in thickness, resulting in poor flatness of the wound core, and the thickest part will be more severely squeezed after hot pressing. Since the solid electrolyte is easily oxidized and decomposed to generate gas under high temperature and high voltage conditions, the gas release path is blocked, resulting in an easy increase in the thickness of the wound core in a high-temperature environment. In this application, by arranging the projections of the adhesive and the positive electrode tab in a dislocation manner (i.e., non-overlapping) in the thickness direction of the wound core, the flatness of the wound core is good, the gas conduction path is unobstructed, and it is prevented that local gas cannot be exported, resulting in interface separation and an increase in the thickness expansion change rate of hot-PPG, and even causing the failure of the battery cell. The addition of the solid electrolyte improves the low-temperature discharge performance, and the dislocation arrangement of the adhesive and the positive electrode tab can avoid the influence of the high-temperature gas generation of the solid electrolyte on the high-temperature safety, so that the battery of this application has both good low-temperature discharge performance and high-temperature safety.

[0096] In some embodiments, the distance between the projections of the negative electrode tab and the adhesive in the thickness direction of the wound core is equal to S, and its function is as described above, so it will not be elaborated here.

[0097] In some embodiments, the bonding member has a first end close to the positive tab along the height direction of the core, and the positive current collector has a second end close to the positive tab along the height direction of the core. The distance between the first end and the second end along the height direction of the core is K, satisfying 125 mm ≥ K > 15 mm. Since the lower edge where the positive tab is welded to the positive electrode sheet is not visible to the naked eye, it is difficult to judge the value of S. K is the distance from the upper edge of the bonding member to the upper edge of the current collector, which is more intuitive and easier to measure. Controlling K to be > 15 mm can make the projections of the bonding member and the positive tab misaligned in the thickness direction of the core, avoiding the increase in thickness caused by the coincidence of the bonding member and the tab, so that the core has good flatness, the gas conduction path is unobstructed, and the increase rate of the thickness expansion of the thermal-PPG is prevented. The addition of the solid electrolyte improves the low-temperature discharge performance, and controlling K to be > 15 mm can make the bonding member and the positive tab misaligned, thus avoiding the influence of the gas generated by the solid electrolyte at high temperature on the high-temperature safety, so that the battery of the present application has good low-temperature discharge performance and high-temperature safety at the same time. Exemplarily, K can be 16 mm, 18 mm, 20 mm, 25 mm, 50 mm, 100 mm, 125 mm, etc. or a value within the range composed of any two of the above values.

[0098] In some embodiments, the bonding member includes a hot melt adhesive, which has good high-temperature resistance and can still have good bonding effect at a relatively high temperature to ensure the bonding effect between the core and the housing, so that the lithium-ion secondary battery of the present application can meet the high-temperature storage requirements. Exemplarily, the hot melt adhesive can be at least one of polyamide, polyester, polyethylene, and polyester amide.

[0099] The following further describes the present application in detail with specific embodiments, and these embodiments should not be construed as limiting the scope claimed by the present application.

[0100] The solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (abbreviated as LATP) used in Examples 1 - 19 is prepared as follows:

[0101] According to the stoichiometric ratios of Li, Al, Ti, and P in Li 1.3 Al 0.3 Ti 1.7 (PO4)3, weigh Li2CO3, AlOOH, TiO2, and NH4H2PO4, mix them, perform ball milling with anhydrous ethanol as the solvent. After ball milling, the raw materials are dried for 5 h. Place the raw materials in a corundum crucible, first calcine at 300 °C for 2 h, then calcine at 700 °C for 4 h. The solid substance obtained after calcination is ball milled again, and after drying and sieving, white LATP powder is obtained.

[0102] Example 1

[0103] This embodiment provides a method for preparing a secondary battery, including:

[0104] First step: Preparation of the positive electrode sheet: Mix lithium cobaltate, solid electrolyte LATP, the first conductive agent, and PVDF (polyvinylidene fluoride) in a mass ratio of 96.52:0.48:1:2, and add NMP, stir evenly to prepare a positive electrode slurry; coat the positive electrode slurry on both the front and back surfaces of the aluminum foil, and after baking and rolling, obtain a positive electrode sheet with a thickness of 100 μm; a slot with a fixed size is provided at a certain position of the positive electrode sheet, and the nickel pole ear (positive pole ear 2) is laser-welded into this slot.

[0105] In this embodiment, the lithium cobaltate includes Ti element and Al element, where the Ti content is 300 ppm and the Al element content is 7000 ppm. The weight of LATP accounts for 0.5% of the weight of lithium cobaltate. The first conductive agent includes carbon nanotubes and carbon black with a mass ratio of 1:1; the diameter of the carbon nanotubes is 20 nm.

[0106] Second step: Mix the negative electrode active material with the second conductive agent, CMC-Li (lithium carboxymethyl cellulose), and PAA (polyacrylic acid) in a mass ratio of 97:0.4:0.1:2.5, and add deionized water to prepare a negative electrode slurry; coat the negative electrode slurry on both the front and back surfaces of the copper foil coated with carbon, and after baking and rolling, obtain a negative electrode sheet with a thickness of 110 μm. A slot with a fixed size is provided at a certain position of the negative electrode sheet, and the copper-nickel plated pole ear is laser-welded into this slot;

[0107] The negative electrode active material includes silicon-carbon and graphite. The weight of silicon-carbon accounts for 8% of the weight of graphite, and the mass content of silicon element in silicon-carbon is 70%; the second conductive agent includes single-walled carbon nanotubes and carbon black with a mass ratio of 1:1, and the diameter of the single-walled carbon nanotubes is 10 nm.

[0108] Third step: After slitting and sheet-making the positive and negative electrode sheets, wind them with the separator to obtain a core;

[0109] Fourth step: Then, a bonding member 1 (hot melt adhesive) is provided on one side in the thickness direction of the core, and it is encapsulated with an aluminum-plastic film, and then baked, filled with electrolyte, formed, second-sealed, sorted, and OCV measured to obtain a lithium-ion secondary battery.

[0110] Among them, the electrolyte is a self-made electrolyte. Mix ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) in a weight ratio of 1:3:6 as the base solvent, and then dissolve ethyl propionate and lithium salt LiPF6 in the above base solvent to obtain the electrolyte, where the mass content of ethyl propionate (EP) is 40%.

[0111] The parameters of the secondary batteries prepared in each embodiment and comparative example are shown in Table 1 and Table 2.

[0112] Among them, the content of Ti element in the solid electrolyte is measured by EDS.

[0113] Table 1 Parameters of Each Example and Comparative Example

[0114]

[0115]

[0116] Table 2 Parameters of Each Example and Comparative Example

[0117]

[0118]

[0119] The SEM image of the positive electrode sheet of Example 5 is as Figure 1 shown, and the enlarged image is as Figure 2 shown. It can be seen from Figure 2 that there are lithium cobaltate particles 4 with a maximum diameter in the range of 8 μm to 40 μm within a vertical distance of 0 to 6 μm from the edge of the solid electrolyte particles 3.

[0120] The difference between Example 20 and Example 1 is that the solid electrolyte is lithium lanthanum titanium oxide (LLTO, Li 0.3 La 0.567 TiO3), the mass content of Ti element in the solid electrolyte is 26%, A = 7000, and A / B = 14.29%.

[0121] The difference between Example 21 and Example 1 is that the solid electrolyte is Li 1.5 Al 0.5 Ti 1.5 (PO4)3, the mass content of Ti element in the solid electrolyte is 16%, A = 7150, and A / B = 14.22%.

[0122] The difference between Example 22 and Example 1 is that the solid electrolyte is Li 1.01 Al 0.01 Ti 1.99 (PO4)3, the mass content of Ti element in the solid electrolyte is 24%, A = 7070, and A / B = 14.38%.

[0123] The lithium-ion secondary battery of Comparative Example 1 is basically the same as that of Example 17, except that LATP is not doped in Comparative Example 1.

[0124] Lithium-ion secondary battery performance test method:

[0125] 1. The test method for the low-temperature discharge performance at -20°C is as follows: Constant current and constant voltage charge the secondary battery at 0.2C at room temperature until the upper limit voltage, cut off at 0.02C, let it stand for 5 minutes, then discharge at 0.2C until 3.0V, record the discharge capacity C1. Then, constant current and constant voltage charge the battery at 0.2C at room temperature until the upper limit voltage, cut off at 0.02C until fully charged. Put the fully charged battery into a -20°C constant temperature chamber or incubator, let it stand for 2 hours, then discharge at 0.2C until 3.0V, record the discharge capacity C2. C2 / C1 is the retention rate of the low-temperature discharge capacity at 0.2C and -20°C.

[0126] 2. Thermal-PPG thickness expansion change rate: Constant current and constant voltage charge the secondary battery at 0.2C at room temperature until the upper limit voltage, cut off at 0.02C. Measure the first thickness h1 using 600 ppg (representing a pressure of 600 g in the standard). Then place it under the condition of 60°C ± 2°C and store for 35 days. After taking out the secondary battery, immediately measure the thickness h2. h2 / h1 is the thermal-PPG thickness expansion change rate.

[0127] 3. Test of volume energy density (ED): Volume energy density ED = E / V, where E is the discharge energy of the battery. The test method is as follows: Charge the lithium-ion secondary battery at a current of 0.2C until the upper limit voltage, then charge at a constant voltage until the current drops to 0.02C. Then discharge at a current of 0.2C until 3.0V. The discharged energy is E. V is the volume of the lithium-ion secondary battery. By measuring the thickness, width, and length of the battery and calculating the product of the three, the volume of the battery is obtained. E / V is the volume energy density obtained from the test.

[0128] The test results are shown in Table 3.

[0129] Table 3 Performance of Lithium-Ion Secondary Batteries in Each Example and Comparative Example

[0130]

[0131]

[0132] As can be seen from the comparison between the examples in Table 3 and Comparative Examples 1-4, the thermal-PPG thickness expansion change rate of the lithium-ion secondary battery of the present application is below 15%, and at the same time, the low-temperature discharge capacity retention rate is above 59%. The low-temperature discharge performance of the secondary battery of the present application is significantly improved, and it has good high-temperature performance while having excellent low-temperature performance. In Comparative Example 1, no solid electrolyte was added, and the low-temperature performance of the secondary battery was poor. As can be seen from Comparative Examples 2 and 3, if the maximum particle size D1 of the solid electrolyte is too small, it is easy to agglomerate by itself, the dispersion is uneven, and the local conductivity is poor; if the maximum particle size D1 of the solid electrolyte is too large, the large-particle solid electrolyte itself has poor conductivity, and the ability to improve the overall low-temperature discharge performance of the battery core is poor. Therefore, adding a solid electrolyte with a maximum particle size D1 in the range of 500 nm to 3 μm to the positive active layer of the secondary battery can significantly improve the low-temperature performance of the battery. As can be seen from the comparison between Example 3 and Comparative Example 5, the particle size Dv10 of lithium cobaltate being greater than the average particle size D2 of the solid electrolyte can further improve the low-temperature discharge performance of the battery.

[0133] Obviously, the above examples are merely illustrations given for clarity and are not limitations on the implementation manners. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to enumerate all the implementation manners here. And the obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A lithium-ion secondary battery, comprising a positive electrode sheet and a negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector, the negative electrode active layer comprises a negative electrode active material, the negative electrode active material comprises a silicon-carbon material and graphite, and based on the mass of the negative electrode active layer, the content of silicon element is C, and C is 1% to 20%; The positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active layer comprises a positive electrode active material and a solid electrolyte, and the maximum particle size D1 of the solid electrolyte is 500 nm to 3 μm; The solid electrolyte includes a Ti element, and the mass content of the Ti element in the solid electrolyte is 2% to 40%; The positive electrode active material includes lithium cobalt oxide, and the lithium cobalt oxide includes Ti and Al elements; the particle size Dv10 of the lithium cobalt oxide is greater than the average particle size D2 of the solid electrolyte; Based on the mass of the positive electrode active layer, the content of the Ti element is Appm, and the content of the Al element is Bppm, satisfying 0.05<A / B≤0.

3.

2. The lithium-ion secondary battery according to claim 1, characterized in that: At least one of the following conditions is met: (1) 0.1≤A / B≤0.2; (2) The maximum particle size D1 of the solid electrolyte is 0.5 μm to 2 μm; (3) The silicon content C in the negative electrode active layer is 1% to 20%; (4) The ratio of the mass content Appm of the Ti element in the positive electrode active layer to the mass content C of the silicon element in the negative electrode active layer satisfies 1250≤A / C≤130000.

3. The lithium ion secondary battery according to claim 1 or 2, characterized in that: The solid electrolyte includes at least one of lithium aluminum titanium phosphorus oxide and lithium lanthanum titanium oxide; And / or, the mass content of the solid electrolyte in the positive electrode active layer is 0.1% to 2%.

4. The lithium ion secondary battery according to claim 1 or 2, characterized in that: The lithium cobalt oxide includes first particles, the particle size D3 of the first particles is 8 μm to 40 μm; a plurality of solid electrolyte particles are distributed around the first particles, and the vertical distance between the solid electrolyte particles and the first particles is 0 to 6 μm.

5. The lithium ion secondary battery according to claim 1 or 2, characterized in that: The content of the Ti element in the positive electrode active layer Appm satisfies 500≤A≤2000; And / or, the content B ppm of the Al element in the positive electrode active layer satisfies 5000≤B≤10000; And / or, the particle size Dv10 of the lithium cobalt oxide is 2 μm to 5 μm; And / or, the median particle size Dv50 of the lithium cobalt oxide is 10 μm to 20 μm.

6. The lithium-ion secondary battery according to claim 1, characterized in that: The positive electrode active layer further includes a first conductive agent, the first conductive agent includes carbon nanotubes, and the diameter of the carbon nanotubes is 5nm to 100nm; Preferably, based on the mass of the positive electrode active layer, the content of the carbon nanotubes is 0.1% to 2%.

7. The lithium-ion secondary battery according to claim 1, characterized in that: At least one of the following conditions is met: (1) The mass content of silicon in the silicon-carbon material is 35% to 70%; (2) The graphite includes one or more of artificial graphite and natural graphite; (3) The silicon-carbon material comprises a carbon substrate and silicon particles dispersed in the pores of the carbon substrate; (4) The negative electrode active layer further includes a second conductive agent, the second conductive agent includes single-walled carbon nanotubes, and the diameter of the single-walled carbon nanotubes is 1 to 50 nm.

8. The lithium-ion secondary battery according to claim 1, characterized in that: The lithium ion secondary battery further comprises an electrolyte, the electrolyte comprises a solvent, the solvent comprises ethyl propionate, and the content of the ethyl propionate is 20% to 60% based on the mass of the electrolyte.

9. The lithium-ion secondary battery according to claim 1, characterized in that: The positive electrode sheet further includes a positive electrode tab, the positive electrode tab is electrically connected to the positive electrode collector, and the positive electrode tab extends from one side in the width direction of the positive electrode collector; The lithium-ion secondary battery also includes a separator, and the positive electrode sheet, the separator and the negative electrode sheet are stacked and wound into a core; an adhesive is provided on at least one side surface of the core in the thickness direction, and the projections of the adhesive and the positive electrode ear in the thickness direction of the core are staggered along the height direction of the core.

10. The lithium-ion secondary battery according to claim 9, characterized in that: The shortest distance between the projection of the positive electrode tab and the bonding member in the thickness direction of the winding core is S, which satisfies 100 mm ≥ S > 0; And / or, the adhesive member has a first end close to the positive electrode ear along the height direction of the core, the positive electrode collector has a second end close to the positive electrode ear along the height direction of the core, and the distance between the first end and the second end along the height direction of the core is K, satisfying 125mm≥K>15mm.

Citation Information

Cited By

  • Battery case, battery, battery pack, and electric device

    CN122659425A